The Endless Wars: Severe Fever With Thrombocytopenia Syndrome Virus, Host Immune and Genetic Factors - Wang, Min; Tan, Weilong; Li, Jun; Fang, Liqun; Yue, Ming (Frontiers in Cellular and Infection Microbiology, 2022)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging arboviral infectious disease with a high rate of lethality in susceptible humans and caused by severe fever with thrombocytopenia syndrome bunyavirus (SFTSV). Currently, neither vaccine nor specific antiviral drugs are available. In recent years, given the fact that both the number of SFTS cases and epidemic regions are increasing year by year, SFTS has become a public health problem. SFTSV can be internalized into host cells through the interaction between SFTSV glycoproteins and cell receptors and can activate the host immune system to trigger antiviral immune response. However, SFTSV has evolved multiple strategies to manipulate host factors to create an optimal environment for itself. Not to be discounted, host genetic factors may be operative also in the never-ending winning or losing wars. Therefore, the identifications of SFTSV, host immune and genetic factors, and their interactions are critical for understanding the pathogenic mechanisms of SFTSV infection. This review summarizes the updated pathogenesis of SFTS with regard to virus, host immune response, and host genetic factors to provide some novel perspectives of the prevention, treatment, as well as drug and vaccine developments.